2016
DOI: 10.1073/pnas.1608808113
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling determines the fate of uterine stroma in the mouse Müllerian duct

Abstract: The Müllerian duct develops into the oviduct, uterus, and vagina, all of which are quite distinct in their morphology and function. The epithelial fate of these female reproductive organs in developing mice is determined by factors secreted from the stroma; however, how stromal differentiation occurs in the female reproductive organs derived from the Müllerian duct is still unclear. In the present study, roles of retinoic acid (RA) signaling in developing female reproductive tracts were investigated. Retinol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…This hypothesis was confirmed in a reporter mouse expressing lacZ regulated by a strong RARE in the promoter. The data demonstrated that the highest endogenous RA levels are in the proximal Müllerian duct stroma, and the levels gradually decrease from the proximal to caudal regions (Nakajima et al 2016). Thus, RA is produced and acts in the stroma of proximal and middle Müllerian ducts.…”
Section: Retinoid Action In Endometrial Differentiation and Developmentmentioning
confidence: 84%
See 4 more Smart Citations
“…This hypothesis was confirmed in a reporter mouse expressing lacZ regulated by a strong RARE in the promoter. The data demonstrated that the highest endogenous RA levels are in the proximal Müllerian duct stroma, and the levels gradually decrease from the proximal to caudal regions (Nakajima et al 2016). Thus, RA is produced and acts in the stroma of proximal and middle Müllerian ducts.…”
Section: Retinoid Action In Endometrial Differentiation and Developmentmentioning
confidence: 84%
“…In fetal mice, Rdh10 and Aldh1a2 are expressed in the stroma of proximal Müllerian ducts, with expression levels decreasing toward the caudal ends (Nakajima et al 2016). RDH10 is the primary enzyme responsible for catalyzing the conversion of retinol to retinaldehyde, the first step of RA synthesis, in embryonic mice (Farjo et al 2011).…”
Section: Retinoid Action In Endometrial Differentiation and Developmentmentioning
confidence: 99%
See 3 more Smart Citations